2009
DOI: 10.1016/j.atherosclerosis.2009.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of antioxidant enzymes in ApoE-deficient mice suppresses Benzo(a)pyrene-accelerated atherosclerosis

Abstract: The carcinogenic polycylic aromatic hydrocarbon, benzo(a)pyrene (BaP), has been shown to generate reactive oxygen species (ROS) and accelerate the development of atherosclerosis. To assess the causal role of BaP-generated ROS in this process, we evaluated atherosclerotic metrics in apolipoprotein E-deficient (ApoE-/-) mice with or without overexpression of Cu/Zn-superoxide dismutase (Cu/Zn-SOD) and/or catalase. Without BaP, aortic atherosclerotic lesions were smaller in ApoE-/- mice overexpressing catalase or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 28 publications
5
47
0
Order By: Relevance
“…For example, SOD overexpression along with CAT decreased Benzo[a]pyrene-induced atherosclerosis in ApoE −/− mice 34) . It was suggested that increased SOD may reduce atherosclerosis through the co-activation of vascular relaxation mediated by nitric oxide (NO) as the radical O2 dismutation increases the bioavailability of NO in endothelial cells; in the presence of the O2 radical, NO shifts to the formation of peroxide nitrite 34) . The aerobic exercise protocol employed in the present study increased CAT activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, SOD overexpression along with CAT decreased Benzo[a]pyrene-induced atherosclerosis in ApoE −/− mice 34) . It was suggested that increased SOD may reduce atherosclerosis through the co-activation of vascular relaxation mediated by nitric oxide (NO) as the radical O2 dismutation increases the bioavailability of NO in endothelial cells; in the presence of the O2 radical, NO shifts to the formation of peroxide nitrite 34) . The aerobic exercise protocol employed in the present study increased CAT activity.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, Fukao et al 31) demonstrated that voluntary exercise decreases atherosclerosis with no change in TC and TG serum levels. It is noteworthy that in ApoE −/− mice the decrease in the atherosclerotic lesion induced by Benzo(a)pyrene may occur with no changes in TC and TG serum levels 34) . Serum levels of TG normally decrease in response to aerobic exercise when a normal chow diet is used.…”
mentioning
confidence: 99%
“…The sooner pitfalls and misinterpretations will be detected, the better both for the benefit of people and to reduce the economic burden associated with death endclinical trials. Lp-PLA2 (-) Inhibition by RNAi [101] and selective inhibitors [102,103] reduced lipid accumulation and progression of coronary atherosclerosis in various atherogenic experimental models PCSK9 (-) Inhibition by alirocumarib reduced LDL levels [1] Oxidative stress related enzymes NADPH oxidase (-) NOX1/4 inhibitor GKT136901 reduced ROS [119,120]; NOX1/2 inhibitor apocynin reduced aortic lesions in apoE-/-LDLR-/-mice [121] Nitric Oxide Synthase (+) Adenovirus-mediated iNOS gene transfer studies showed that local NO synthesis induced significant proliferation of SMCs and intimal hyperplasia in rats [135] Superoxide dismutases (+) SOD local delivery decreased the cuff-induced arterial neointima [138], accelerated endothelial recovery and inhibited in-stent restenosis in the aorta of Watanabe rabbits [139]; mitochondrial SOD protected apoE-/-mice against atherosclerosis [140,141] Catalases (+) Overexpression retarded atherosclerosis development in apoE-/-mice [141]; dietary supplements upregulated CAT expression in apoE-/-mice and reduced atherosclerosis [144,145]; CAT attenuated non-dietary atherosclerosis in apoE-/-mice [146] Glutathione peroxidases (+) Mimetic diphenyl diselenide reduced atherosclerotic lesions in LDLR-/-mice [153] Heme oxygenase-1 (+) Inducers hemin±desferrioxamine reduced atherosclerotic lesions in LDLR-/-mice [164] Paraoxonases (+) Reduced protein N-homocysteinylation, prevented accumulation of oxLDL, promoted cholesterol efflux from macrophages [173], improved endothelial function [174] Vascular remodeling related enzymes Matrix Metalloproteases (-)/(+) Area of aortic calcified lesions was reduced in apoE-/-/MMP2-/-mice compared to apoE-/-mice ( [192]); apoE-/-/MMP-3-/-and apoE-/-/MMP-9-/-mice had larger brachiocephalic artery plaques [193], while lesion size was reduced in apoE-/-/MMP-12-/-mice [193] Inflammation related enzymes Cyclooxygenase (-) COX-1 knockout in apoE-/-mice reduced platelet-vascular wall interactions and decreased lesions [203] Lipoxygenase (-) 12/15 LO knockout in macrophages impaired oxLDL-induced foam cell formation and endothelial activation …”
Section: Resultsmentioning
confidence: 99%
“…CAT is also powerful in the attenuation of non-dietary atherosclerosis in apoE-deficient mice. Thus, its overexpression in apoE mice exposed to the polycyclic aromatic hydrocarbon benzopyrene, alone or in association with Cu/Zn-SOD, led to increased protection as compared with those overexpressing only Cu/Zn-SOD [146].…”
Section: Catalasesmentioning
confidence: 99%
“…By converting hydrogen peroxide into water, CAT constitutes a primary antioxidant defense system and could protect cells from ROS and its deleterious consequences 31 . In experimental setting, CAT leads to a delayed onset of atherosclerosis in a murine model 32 . Besides, longer-liver mice have more abundant expression of CAT in aortas when compared to shorter-lived mice, but expression of SOD was similar in both groups 10 .…”
Section: Discussionmentioning
confidence: 99%